Climate change 2014 : mitigation of climate change. Summary for policymakers and technical summary (D2312) - Edenhofer, O. Pichs-Madruga, Ramon., Sokana, Youba., Minx, Jan C., Farahani, E., Kadner, S., & Seyboth, K. (Cambridge University Press : USA, 2014)
The Working Group II contribution to the IPCC$1 (Bs Fifth Assessment Report (AR5) assesses literature on the scientific, technological, environmental, economic and social aspects of mitigation of climate change since 2007 when the Fourth Assessment Report (AR4) was releaseds
Includes annexures.
Keywords: Earth and Environmental Sciences, Climatology and Climate Change